Differences in school factors associated with adolescent HPV vaccination initiation and completion coverage in three Australian states. Issue 41 (1st October 2021) - Sisnowski, J.; Vujovich-Dunn, C.; Gidding, H.; Brotherton, J.; Wand, H.; Lorch, R.; Veitch, M.; Sheppeard, V.; Effler, P.; Skinner, S.R; Venn, A.; Davies, C.; et al.
Abstract: Background: Schools are the primary setting for the delivery of adolescent HPV vaccination in Australia. Although this strategy has achieved generally high vaccination coverage, gaps persist for reasons that are mostly unknown. This study sought to identify school-level correlates of low vaccination course initiation and completion in New South Wales, Tasmania, and Western Australia to inform initiatives to increase uptake. Methods: Initiation was defined as the number of first doses given in a school in 2016 divided by vaccine-eligible student enrolments. Completion was the number of third doses given in a school in 2015–2016 divided by the number of first doses. Low initiation and completion were defined as coverage ≤ 25th percentile of all reporting schools. We investigated correlations between covariates using Spearman's rank correlation coefficients. Due to multicollinearity, we used univariable logistic regression to investigate associations between school characteristics and low coverage. Results: Median initiation was 84.7% (IQR: 75.0%-90.4%) across 1, 286 schools and median completion was 93.8% (IQR: 86.0%-97.3%) across 1, 295 schools. There were strong correlations between a number of school characteristics, particularly higher Indigenous student enrolments and lower attendance, increasing remoteness, higher postcode socioeconomic disadvantage, and smaller school size. Characteristics most strongly associated with low initiation in univariate analyses were small school size, location in Tasmania, and schools catering for special educational needs. Low completion was most strongly associated with schools in Tasmania and Western Australia, remote location, small size, high proportion of Indigenous student enrolments, and low attendance rates. Conclusion: This study provides indicative evidence that characteristics of schools and school populations are associated with the likelihood of low initiation and completion of the HPV vaccination course. The findings will guide further research and help target initiatives to improve vaccination uptake in schools with profiles associated with lower coverage.